The Influence of the Spider Web Learning Model on Learning Achievement in Basic Mathematics for Children with Mental Disabilities - Irmawati, Irmawati; Putro, Khamim Zarkasih (The Center for Disability Studies and Services Brawijaya University, 2022)
The purpose of the research was to determine the effect of using the spider web learning model on the improvement of learning achievement in basic mathematics for children with mental disabilities in a Kindergarten in Central Java. The research uses an experimental method with a one-group pretest-posttest design, in which a group of subjects is treated for a certain period and the effect of treatment is measured from the difference between the initial measurement (pretest) and the final measurement (posttest). The research subjects were all children in group B with a total of five students. Data collection techniques using tests. Data analysis used the Wilcoxon signed-rank test analysis technique. The result of the research is that the Z account value is -2.027 with Asymp. Sign (2-tailed) 0.043 at a significant level (α) 0.05 or 5%. For this reason, it can be concluded that the use of the spider web learning model affects increasing learning achievement.